2017
DOI: 10.1001/jamaophthalmol.2017.0043
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Smoking During Pregnancy and Birth Weight With Retinal Nerve Fiber Layer Thickness in Children Aged 11 or 12 Years

Abstract: IMPORTANCE Both maternal smoking during pregnancy and low birth weight have been implicated in impaired development of the retina. OBJECTIVE To investigate the associations of maternal smoking during pregnancy and low birth weight with retinal nerve fiber layer (RNFL) thickness in preadolescent children. DESIGN, SETTING, PARTICIPANTS The Copenhagen Child Cohort 2000 Eye Study is a prospective, population-based, birth cohort study that included all children (n = 6090) born in 2000 in Copenhagen, Denmark. Matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 38 publications
6
30
0
1
Order By: Relevance
“…5 Rothman and colleagues 6 observed a correlation between brain structure and peripapillary retinal nerve fiber layer (pRNFL) thinning in preterm infants (gestational age < 32 weeks). Scarce population-based data exist regarding the association of low birth weight and pRNFL in childhood, 7 whereas to our knowledge no population-based data exist for this relationship in adulthood.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…5 Rothman and colleagues 6 observed a correlation between brain structure and peripapillary retinal nerve fiber layer (pRNFL) thinning in preterm infants (gestational age < 32 weeks). Scarce population-based data exist regarding the association of low birth weight and pRNFL in childhood, 7 whereas to our knowledge no population-based data exist for this relationship in adulthood.…”
mentioning
confidence: 93%
“…10 In the population-based Copenhagen Child Cohort 2000 Eye Study, thinner pRNFL thickness was found in former low-birth-weight infants (<2500 g; 11 to 12 years of age at the time of the study) compared to former normal birth weight infants (≥2500 g). 7 Thinner pRNFL is associated with various optic neuropathies, particularly glaucoma, which is one of the main eye diseases causing visual impairment and blindness in Western countries. 14 Therefore, gaining knowledge about the factors affecting the pRNFL is of importance and may contribute to a better understanding of potential risk factors for glaucoma.…”
mentioning
confidence: 99%
“…Es mucha la literatura existente acerca de alteraciones a nivel funcional, aunque muy poca relativa a alteraciones orgánicas o morfométricas. En el estudio llevado a cabo por Pueyo et al 24 y posteriormente en el realizado por Ashina et al 25 se demostró que la exposición prenatal al tabaco produce una alteración del desarrollo del nervio óptico en humanos, encontrándose un adelgazamiento de CFNR, independiente del peso al nacer. Estos resultados son congruentes con los encontrados en nuestro estudio, donde las medidas retinianas tomadas en el grupo de los niños cuyas madres fueron fumadoras durante el embarazo fueron peores que las del grupo control, a pesar de no encontrar diferencia estadísticamente significativa, probablemente por contar con un menor número de muestra que en los citados trabajos.…”
Section: Discussionunclassified
“…Previous reports on the CCC2000 eye study cohort cover choroidal and retinal nerve fiber layer thickness and optic disc drusen characteristics [15][16][17][18] and the details of the protocol. 15 In brief, all participants and their parents were asked about the participants' ophthalmic history, and anthropometric measures were obtained including weight and height.…”
Section: Methodsmentioning
confidence: 99%
“…14 The ethnicity of the children was indirectly assessed by the maternal citizenship code as registered in the Danish Civil Registration System as described in a previous report. 16 All subjects underwent a general ophthalmic examination including nonmydriatic fundus photography with fovea-and disc-centered 458 digital color fundus photography (Topcon Mark II TRC-NW7SF; Topcon Corp., Tokyo, Japan). Fundus characteristics were assessed by an ophthalmologist (ICM) who was masked to all parameters.…”
Section: Methodsmentioning
confidence: 99%